OA02.03. Healers in the context of culture: The ashtavaidya tradition of Kerala, South India. - Leela, PU (Medknow Publications & Media Pvt Ltd, 2013)
PURPOSE: The present paper provides a comprehensive and dynamic profile of Ashtavaidya system of medicine existing in Kerala. It discussed about a traditional group of Vaidyas (specifically Ashtavaidyas) who have inextricable influence on the sociocultural location of traditional healing practices in Kerala. The Ashtavaidyas are the Kerala Brahmin (Namboothiri) practitioners who are specialized in the eight branches of the Ayurveda. Their system of medicine is based on Vagbhata's Ashtangahridyam. METHOD: The study has relied both on primary and secondary resources for data collection. The primary mode of data gathered through personal interviews. Unstructured interviews used for this purpose. As an interviewer, the researcher collected data from the senior Ashtavaidyas of Kerala. In the first phase, the field work was conducted with Ashtavaidya families of pazhanellippurathu Thaikkattu and Elayidath Thaikkattu situated in Thrissur and Chirattamann Illam and Olassa moss in Kottayam district. The second phase of the field work was with Vaidyamadham and Pulamanthol Illam in the northern part of Kerala. Palm leaves and family histories also constitute the primary resources for the study. The secondary sources include books, journals, articles, unpublished materials. RESULT: The sociological significance of this study alludes to the way in which the Ashtavaidya tradition sailed through the myriad historical and cultural conjectures. It also informs us about the internal dynamics and differential social location within a normatively given community which produces both an ‘elevated’ space of priesthood and Vaidyas. CONCLUSION: Cultural factors play a critically important role in health. Social conditions and situations not only promote the possibility of illness and disability, but they also enhance prospects for disease prevention and health maintenance. Individuals and societies tend to respond to health problems in a manner consistent with their culture, norms and values.